Prenatal Nicotine Exposure Alters Lung Function and Airway Geometry through α7 Nicotinic Receptors - Wongtrakool, Cherry (American Thoracic Society, 2012)
Maternal smoking during pregnancy has been associated with adverse effects on respiratory health. Whereas the epidemiologic link is incontrovertible, the mechanisms responsible for this association are still poorly understood. Although cigarette smoke has many toxic constituents, nicotine, the major addictive component in cigarette smoke, may play a more significant role than previously realized. The objectives of this study were to determine whether exposure to nicotine prenatally leads to alterations in pulmonary function and airway geometry in offspring, and whether α7 nicotinic acetylcholine receptors (nAChRs) mediate these effects. In a murine model of in utero nicotine exposure, pulmonary function, airway size and number, methacholine response, and collagen deposition were examined. Exposure periods included Gestation Days 7–21, Gestation Day 14 to Postnatal Day 7, and Postnatal Days 3–15. Prenatal nicotine exposure decreases forced expiratory flows in offspring through α7 nAChR–mediated signals, and the critical period of nicotine exposure was between Prenatal Day 14 and Postnatal Day 7. These physiologic changes were associated with increased airway length and decreased diameter. In addition, adult mice exposed to prenatal nicotine exhibit an increased response to methacholine challenge, even in the absence of allergic sensitization. Collagen expression was increased between adjacent airways and vessels, which was absent in α7 nAChR knockout mice. These observations provide a unified mechanism of how maternal smoking during pregnancy may lead to lifelong alterations in offspring pulmonary function and increased risk of asthma, and suggest potential targets to counteract those effects.